Studies of TLP Dynamic Response Under Wind, Waves and Current - 谷家扬 杨建民 吕海宁 (China ocean engineering, 2012)
Investigated is the coupled response of a tension leg platform （TLP） for random waves. Inferred are the mass matrix, coupling stiffness matrix, damping matrix in the vibration differential equation and external load of TLP in moving coordinating system. Infinitesimal method is applied to divide columns and pontoons into small parts. Time domain motion equation is solved by Runge-Kutta integration scheme. Jonswap spectrum is simulated in the random wave, current is simulated by linear interpolation, and NPD spectrum is applied as wind spectrum. The Monte Carlo method is used to simulate random waves and fluctuated wind. Coupling dynamic response, change of tendon tension and riser tension in different sea conditions are analyzed by power spectral density （PSD）. The influence of approach angle on dynamic response of TLP and tendon tension is compared.